Relationship between Yarn Properties and Process Parameters in False-Twist Textured Yarn - Kenan Yildirim, Ph.D.; Sule Altun, Ph.D.; Yusuf Ulcay, Ph.D. (Journal of Engineered Fibers and Fabrics, 2009)
The properties of false-twist textured yarns in the aspects of crimp characteristic and tensile behavior depend mainly on the draw ratio and the D/Y ratio. This study comprises investigations of the effect of D/Y ratio and draw ratio on the crimp and tensile properties and percent crystallinity. While there was no noticeable change on the percent crystallinity by altering these parameters, tenacity increased and crimp contraction decreased with increasing draw ratio, and crimp stability decreased when the D/Y ratio increased. K/S value also decreased with increasing draw ratio.